Plasmalogens, the Vinyl Ether-Linked Glycerophospholipids, Enhance Learning and Memory by Regulating Brain-Derived Neurotrophic Factor - Hossain, Md. Shamim; Mawatari, Shiro; Fujino, Takehiko (Frontiers in Cell and Developmental Biology, 2022)
Plasmalogens (Pls), a kind of glycerophospholipids, have shown potent biological effects but their role in hippocampus-dependent memory remained mostly elusive. Here, we first report Pls can enhance endogenous expression of brain-derived neurotrophic factor (Bdnf) in the hippocampus and promotes neurogenesis associated with improvement of learning and memory in mice. Genomic and proteomic studies revealed that Pls enhanced recruitment of CREB transcription factor onto the murine Bdnf promoter region via upregulating ERK-Akt signaling pathways in neuronal cells. Reduction of endogenous Pls in murine hippocampus significantly reduced learning and memory associated with the reduction of memory-related protein expression, suggesting that Pls can regulate memory-related gene expression in the hippocampus.